STRATEGI DAN PROGRAM PENGEMBANGAN PEMASARAN PUPUK PT. SRIWIJAYA - Musdirwan Musdirwan; Bheny Rahman Yusri (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2018)
PT. Pupuk Sriwidjaja  is a company that produces urea (CON2H4) and ammonia (NH3) fertilizier. Both products are marketed for domestic and foreign (export) consumption. Especially for urea fertilizier, the sale is through two distribution channels, namely the subsidized agriculture sector and the commercial sector (both domestic and foreign). While ammonia fertilizer is marketed to the commercial sector (both domestic and foreign). PT. Pupuk Sriwidjaja experienced fluctuating sales conditions due to a decrease and growth in sales volume. As for the purpose of the problem, to find out how much percentage (%) of growth or decrease in sales of urea and ammonia fertilizers, find out the marketing development program strategy of PT Pupuk Sriwidjaja. The results showed that, based on the analysis of sales data of PT. Pupuk Sriwidjaja Palembang in 2013-2017, it can be seen that the sales growth of urea fertilizer experienced fluctuating conditions with a growth of 6.08% and ammonia sales experienced a five-year sales growth of 27.79%.